Continuous suturing as a wound closure technique for circumcisions. (November 2019) - Ravindraanandan, Manoj; Fernando, Herman; Aslam, Shahjahan
Male circumcision is an extremely common urological procedure worldwide, with many variations in technique. Despite the large volume there is a low incidence of complications associated with circumcisions, with the majority being Clavien-Dindo I or II. In this study, we analyse the outcomes and complication rates associated with a continuous wound closure following a male circumcision. Methods: In a urology department from a single institution, 201 male circumcisions with a continuous wound closure were performed in a 4-year period. Outcomes were analysed retrospectively looking at postoperative complications and readmissions to hospital via our clinical portal. Results: No patients had complications that required admission or re-operation at our institution. Conclusion: No major post-operative complications were observed from our cohort. There were also no documented admissions back to our institution with wound healing complications. However, a limitation is that Clavien-Dindo I and II complications and treatment at general practitioner surgeries were not captured and may not accurately represent our complication rates quoted. Nevertheless, we can conclude from these data that closure for a circumcision using a continuous suture technique gives favourable outcomes with acceptable complication rates. Level of evidence: Not applicable for this multicentre audit.